2012
DOI: 10.1007/s12262-012-0737-8
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Study about the Anomolous Origin of Testicular Arteries Arising from the Accessory Renal Arteries

Abstract: Testicular arteries are paired vessels, arising from the abdominal aorta, at the level of second lumbar vertebra. Variations in the origin of these vessels highlight a potential importance regarding the vascular supply to the gonads and kidneys. This study was designed to assess the variations in the origin, course, and distance about the point of origin of the testicular arteries. The posterior abdominal walls of 40 male cadavers were studied on either side, during routine dissection in the Department of Anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is noteworthy that Mamatha et al [24] noticed that in 20% of their specimens the variable TAs were associated with accessory renal arteries. In specific, most of these aberrant TAs were originated solely from accessory renal arteries and not main renal arteries.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It is noteworthy that Mamatha et al [24] noticed that in 20% of their specimens the variable TAs were associated with accessory renal arteries. In specific, most of these aberrant TAs were originated solely from accessory renal arteries and not main renal arteries.…”
Section: Discussionmentioning
confidence: 90%
“…Felix [13] found TA's variation incidence being 16/180 (0.09%) in a material of human fetuses. Moreover Mamatha et al [24] found TAs variations in 20%, with the rest cases being normal in their origin, course and number. However, TA's variants regarding their number as well as their course are considered less frequent than the variations of the TVs [5].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations